Hyperperfusion in Carotid Stenting Patients. Issue 3 (May 2015) - Aralasmak, Ayşe; Atay, Musa; Toprak, Huseyin; Ozdemir, Tugce; Asil, Talip; Goktekin, Omer; Mehdi, Elnur; Ozdemir, Huseyin; Alkan, Alpay
<x xml:space="preserve">Abstract</x> Purpose This study aimed to define hyperperfusion in carotid stenting patients without excluding patients with stenosis on the contralateral side. Materials and Methods A total of 32 patients were enrolled. Prestent computed tomography perfusions were performed within 1 week before stenting, poststent perfusions 3 days after stenting. Prestent relative cerebral blood volume, relative cerebral blood flow, and relative mean transient time (rMTT) were calculated by dividing measurements from ipsilateral stent sides to contralateral sides and prestent difference mean transit time (dMTT) by subtracting contralateral mean transient time (MTT) from ipsilateral MTT. Poststent values were calculated similarly. For differences between prestent and poststent values, independent t test was used between groups and paired sample t test within the groups. Results Of the 31 patients, 4 showed poststent clinical hyperperfusion syndrome. Six showed poststent radiologic hyperperfusion with increased cerebral blood flow, increased or spared cerebral blood volume, and shortened MTT values, but only 1 demonstrated clinical hyperperfusion. Between normal and hyperperfused groups, only appreciable difference was noted in prestent and poststent dMTT without statistical significance. Within the groups, only statistical difference (P < 0.001) was noted in rMTT and dMTT in normal groups and no significant difference in the hyperperfused group. Conclusions Radiologic hyperperfusion does not match clinical hyperperfusion. Normal group responded to stenting with statistically significant changes of rMTT and dMTT. Hyperperfusion mostly occurred in the contralateral critically stenosed patients. The hyperperfused group, due to similar MTT of both hemispheres and ipsilateral internal carotid artery being the main feeder of both hemispheres, did not show significant changes in their rMTT and dMTT values after stenting. This shows that reduced hemodynamic reserve is the main reason behind the hyperperfusion after carotid stenting.